2020
DOI: 10.1186/s13023-020-01580-9
|View full text |Cite
|
Sign up to set email alerts
|

English version of the self-administered Fabry Pain Questionnaire for adult patients

Abstract: Background Pain is an early symptom of Fabry disease (FD) and is characterized by a unique phenotype with mainly episodic acral and triggerable burning pain. Recently, we designed and validated the first pain questionnaire for adult FD patients in an interview and a self-administered version in German: the Würzburg Fabry Pain Questionnaire (FPQ). We now report the validation of the English version of the self-administered FPQ (enFPQ). Methods After two forward–backward translations of the FPQ by native Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several study participants reported that this questionnaire failed to give a true picture of their general pain burden related to FD. Recently translated into English, 82 the Würzburg Fabry Pain Questionnaire 33 might prove a useful tool, but a validated Norwegian translation is not yet available. Another limitation to be acknowledged is that the HADS questionnaire has not been validated for use in FD.…”
Section: Discussionmentioning
confidence: 99%
“…Several study participants reported that this questionnaire failed to give a true picture of their general pain burden related to FD. Recently translated into English, 82 the Würzburg Fabry Pain Questionnaire 33 might prove a useful tool, but a validated Norwegian translation is not yet available. Another limitation to be acknowledged is that the HADS questionnaire has not been validated for use in FD.…”
Section: Discussionmentioning
confidence: 99%